Antecedent of Emotional Quotient, Spiritual Quotient, and Emotional Spiritual Quotient (ESQ) among Boarding Schools and Higher Learning Institutions Students - Che Su Mustaffa; Nuredayu Omar; Munif Zarrirudin Fikri Nordin (Journal of Techno-Social, 2011)
Emotional and spiritual quotient plays a principal role in life especially among students which enables them to overcome challenges in their life. This research was conducted in order to answer the question, “To what extent does family communication and institutional communication relate with students’ nemotional and spiritual qoutients?” A quantitative design was employed to examine different variables in those relationships among students. Augustian’s Emotional Spiritual Quotient Instrument (2001), and Ritchie and Fitzpatrick’s Family Communication and Institutional Communication Instrument (1990) were adapted and employed in this study. A total of 404 participants from Malaysian Higher Learning nInstitutions (IPT) and 699 respondents from Malaysian Boarding Schools (SBP) participated in this nresearch. Questionnaires were distributed to gather the data and were analysed using mean score, ncorrelation, t-test, and One-Way ANOVA through SPPS version 11.0. The research findings indicated thatn the emotional and spiritual quotient level. The differences in term of emotional and spiritual quotient found namong these student groups were gender among SBP students, and age among IPT students.